Effect of Cervical Cancer Education and Provider Recommendation for Screening: A Systematic Review - Tetti Solehati; Bhekti Imansari; Devita Madiu; Cecep Eli Kosasih; Yanti Hermayanti; Henny Suzana Mediani (Universitas Aisyah Pringsewu, 2020)
The incidence of cervical cancer in the world is still high as well as in Indonesia. This cancer affected women's physically, psychologically, socially, sexually functionally, and spiritually. The purpose of this review literature was to determine the effect of cervical cancer education and to identify the effects of provider recommendations for screening to eligible women, as a basis for developing new interventions for nurses. We used the PICO (Problem or Population, Interventions, Comparison and Outcome) framework to develop our search strategy. Searching for articles was done through four English databases namely CINAHL, Science Direct, Pubmed, and Proquest to identify articles published between 2009-2019. Of the 2,665 filtered research reports, 14 articles were found that met the requirements. The data synthesis and reporting was guided by the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA). Results, there were eight randomized control trials, five quasi-experiment, and one mixed method involved in the analysis step. The interventions were cervical cancer screening methods (1 article), interventions to increase participation in cervical cancer screening (10 articles), postoperative cervical cancer nursing interventions (1 article), and interventions handling symptoms or problems due to cervical cancer (2 articles). Our findings supported the implementation of cervical cancer educational interventions to increase women's participation in cervical cancer screening programs. Nurses and midwifery have the opportunity to innovate interventions related to nursing, through research in order to improve the quality of nursing care for patients. Abstrak: Insiden kanker serviks di Indonesia maupun di dunia masih cukup tinggi. Wanita dengan kanker serviks dapat mengalami perubahan secara fisik, psikologis, social dan fungsi seksual, maupun spiritual. Tujuan literatur review ini untuk mengetahui pengelolaan kanker serviks, sebagai dasar pengembangan intervensi baru oleh perawat pada pasien kanker serviks. Pencarian artikel dilakukan melalui empat database yaitu CINAHL, Science Direct, Pubmed dan Proquest. Pencarian data elektronik dilakukan pada bulan September 2019. Didapatkan 15 artikel yang sesuai dengan tema dan kriteria inklusi. Hasil, satu artikel tentang metode skrining kanker serviks, sepuluh artikel tentang intervensi untuk meningkatkan partisipasi skrining kanker serviks, dua artikel tentang intervensi keperawatan post operasi kanker serviks, dan dua artikel tentang intervensi penanganan gejala atau masalah akibat kanker serviks. Masih sedikit intervensi yang dikembangkan oleh perawat, terkait pengelolaan kanker serviks. Perawat memiliki peluang untuk melakukan inovasi intervensi terkait keperawatan, melalui penelitian agar dapat meningkatkan kualitas asuhan keperawatan dan kepuasan pasien.